Dignity as borderline value for tolerance - Zalewska-Pawlak, Mirosława; Sieczych-Kukawska, Aleksandra (Granice tolerancji w sztuce i w wychowaniu, 2020)
Purpose of undertaken considerations is presentation of existing dependencies between dignity and tolerance in educational contexts. Person’s dignity is too frequently violated and tolerance overinterpreted for one’s egoistical purposes or to hide society’s indifference. Following issues were highlighted: theoretical basis for defining dignity and tolerance as well as their consequences for education.